The Use of Grape Pomace Residues as a Nutrient Source in Subtropical Viticulture - Allan Augusto Kokkonen; Tadeu Luis Tiecher; Arcângelo Loss; Moreno Toselli; Luana Paula Garlet; Ana Luiza Lima Marques; Daniéle Gonçalves Papalia; Samuel Schemmer; Vanessa Ferraz Costa; Jean Michel Moura-Bueno; Gustavo Brunetto (Agronomy)
The global wine industry is shifting towards organic viticulture to reduce dependence on industrial inputs, favoring organic nutrient sources like grape pomace. However, the suitability of grape pomace-based compost and vermicompost in subtropical regions remain unclear. Given the diverse responses of grapevines to fertilization under different climates and soil conditions, field studies are crucial. This research investigated whether these residues, alongside non-industrialized mineral fertilizers, can enhance soil fertility and improve grape yield and quality in subtropical climates. We found that compost and vermicompost exhibit distinct chemical compositions, leading to varied patterns of nutrient release in soils. However, grapevines displayed minimal to negligible responses in terms of leaf tissue levels nutrients. Notably, “Isabella” grapevines displayed a reduction in grape yield with organic fertilizer application and remained unresponsive to mineral fertilization. While there were no substantial alterations in must composition, “Isabella” grapevines demonstrated elevated levels of anthocyanins when cultivated with mineral fertilizer. In contrast, “Chardonnay” grapevines exhibited no changes in both grape yield and quality in response to the various fertilization treatments examined. While organic and mineral fertilizers may have distinct chemical compositions and release patterns, their effectiveness in improving grape yield and quality appears to vary significantly among different grape cultivars.